The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.5307/jbe.2013.38.4.279
|View full text |Cite
|
Sign up to set email alerts
|

Utilization Efficiencies of Electric Energy and Photosynthetically Active Radiation of Lettuce Grown under Red LED, Blue LED and Fluorescent Lamps with Different Photoperiods

Abstract: This study was conducted to analyze the utilization efficiencies of electric energy and photosynthetically active radiation of lettuce grown under red LED, blue LED and fluorescent lamps with different photoperiods. Methods: Red LED with peak wavelength of 660 nm and blue LED with peak wavelength of 450 nm were used to analyze the effect of three levels of photoperiod (12/12 h, 16/8 h, 20/4 h) of LED illumination on light utilization efficiency of lettuce grown hydroponically in a closed plant production syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
(15 reference statements)
3
5
0
Order By: Relevance
“…Initial increase in SDW, and thereby EUE, with increasing R:B was likely due to a positive effect of greater percentage of red on lettuce growth. Leaf expansion and shoot growth of lettuce were shown to be greater under red light in other studies (Kang et al, 2016;Lee and Kim, 2013;Poulet et al, 2014;Wang et al, 2016;Wojciechowska et al, 2015;Zhang T. et al, 2018). In addition, a negative effect of a greater fraction of blue light on leaf and shoot growth in lettuce was also previously reported (Hoenecke et al, 1992;Tosti et al, 2018).…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Initial increase in SDW, and thereby EUE, with increasing R:B was likely due to a positive effect of greater percentage of red on lettuce growth. Leaf expansion and shoot growth of lettuce were shown to be greater under red light in other studies (Kang et al, 2016;Lee and Kim, 2013;Poulet et al, 2014;Wang et al, 2016;Wojciechowska et al, 2015;Zhang T. et al, 2018). In addition, a negative effect of a greater fraction of blue light on leaf and shoot growth in lettuce was also previously reported (Hoenecke et al, 1992;Tosti et al, 2018).…”
Section: Resultssupporting
confidence: 62%
“…This suggests that EUE can be lower when a greater proportion of red light is emitted by phosphor due to a larger ''down conversion'' involved (blue vs. red) and increased wastage of electrical energy in the form of heat as a result. In contrast, a greater proportion of red light in the incident light may be preferred for lettuce production as it increases leaf expansion and shoot growth (Kang et al, 2016;Lee and Kim, 2013;Wang et al, 2016;Zhang X. et al, 2018). Thus, the spectral quality of LEDs can potentially influence EUE by affecting both SDW and EEC in opposite ways.…”
mentioning
confidence: 99%
“…Son and Oh (2013) also reported the highest fresh weight with the monochromatic R LED treatment, when compared lettuce growing under 100% R and different combinations of R and B light. Lee and Kim (2013) also working with lettuce and comparing fluorescent lamps with red and blue monochromatic LEDs, verified the same trend, fresh and dry weight increased in R and decreased in B, when compared to the fluorescent control.…”
Section: Discussionsupporting
confidence: 57%
“…In a similar study, Hiroki et al [ 14 ] used the same 16-hour light photoperiod but varied the light period from 18 to 24 hours and showed that a shorter period has the best growth in lettuce albeit at the expense of high energy consumption. On the specific effect of photoperiod on lettuce growth, [ 15 ] and [ 16 ] both reported that the preferred photoperiod range is between 16- to 20-hour light. The speed breeding method [ 17 ] introduced by Watson et al, marks the culmination of the importance of photoperiod in improving crop productivity, where the productivity of crops such as wheat and barleys that are subjected to extended light exposure (up to 22-hour light) have been experimentally shown to accelerate by at least twofold [ 17 ].…”
Section: Introductionmentioning
confidence: 99%